2020
DOI: 10.7717/peerj.10304
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of specific stabilization exercise compared with traditional trunk exercise in women with non-specific low back pain: a pilot randomized controlled trial

Abstract: Background Non-specific low back pain (LBP) is the leading cause of disability worldwide. The primary physiotherapeutic treatment for LBP is physical exercise, but evidence suggesting a specific exercise as most appropriate for any given case is limited. Objective To determine if specific stabilization exercise (SSE) is more effective than traditional trunk exercise (TTE) in reducing levels of pain, disability and inflammation in women with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…In the literature, there are very few studies comparing the effectiveness of yoga and stabilization exercises, while there are many studies comparing the effects of these 2 exercises with traditional therapeutic exercises; however, no clear findings were obtained in those studies. It was reported in some studies that they had similar effects,25–27 while some other studies indicated that yoga and stabilization exercises were more effective 28–30. In addition, the results of recent systematic reviews and meta-analyses examining the effects of exercises on CLBP indicate that exercises are not superior to each other 7,8.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there are very few studies comparing the effectiveness of yoga and stabilization exercises, while there are many studies comparing the effects of these 2 exercises with traditional therapeutic exercises; however, no clear findings were obtained in those studies. It was reported in some studies that they had similar effects,25–27 while some other studies indicated that yoga and stabilization exercises were more effective 28–30. In addition, the results of recent systematic reviews and meta-analyses examining the effects of exercises on CLBP indicate that exercises are not superior to each other 7,8.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion criteria were as follows: nonspecific, nonradicular (axial) chronic LBP diagnosis (LBP for at least three months), a Visual Analog Scale (VAS) score of 5 or higher, and sufficient cooperation. The exclusion criteria were determined as specific LBP (presence of a specific cause, such as radiculopathy, spinal stenosis, or infection),[ 4 ] radicular pain, surgical history in the lumbar spine area, vertebral compression fracture, spinal tumors, intervertebral disc infections, inflammatory rheumatic diseases, pregnancy, heart disease, and structural abnormalities in the lumbar region. The patients' age, sex, educational status, height-weight, body mass index (BMI), medications, whether there was any concomitant disease, and the duration of the symptoms were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…This condition is classified as nonspecific LBP and constitutes at least 90% of those experiencing spinal pain; its diagnosis is based on the exclusion of other specific causes. [ 4 - 6 ]…”
Section: Introductionmentioning
confidence: 99%
“…Currently, few studies have specifically observed the specific effect of MCE on LBP from an inflammatory aspect. One research investigated the plasma concentration level changes of TNF-α and IL-6 after long-term MCE intervention among patients with LBP ( 63 ). Their results indicated TNF-α maintained whereas IL-6 increased after intervention.…”
Section: Inflammatorymentioning
confidence: 99%